Enhancing students’ self-efficacy through the sport education–traditional games (se-tg) learning model - Ginanjar, Shela; Samsudin, Samsudin; Rihatno, Taufik; Subandi, Oman Unju (Citius : Jurnal Pendidikan Jasmani, Olahraga, dan Kesehatan, 2025)
The purpose of this study was to see the effect of the use of SE-TG (Sport Education Model-Traditional Games) used in physical education learning at SMK 45 Lembang on Self-Eficacy. The research methodology used is Experimental Designs with Random Assignment sampling. The population in this study were 10 grade XI students of SMK 45 Lembang, totaling 300 people. The sampling technique used was Simple Random Sampling technique, so that 60 students were randomly taken and divided into two groups, where 30 students studied with SE-TG and 30 students studied with the conventional model. The results showed that in the Experimental group, the t-value -4.271, P Value 0.000 and in the control group, the t-value -0.410, P Value 0.681. This means that there was an increase in Self-Eficacy in the experimental group and there was no increase in Self-Eficacy in the control group. The results of the difference test show that for the Self-Eficacy variable, the Z value is -3.190 with P Value 0.001. This means that SE-TG learning has a better influence on Self-Eficacy than the Conventional Model of students at SMK 45 Lembang. For further research, it is very interesting if the concept of the Sport Education Model in collaboration with Traditional Games (SE-TG) can be applied to other physical education materials such as athletics, small ball games, gymnastics and games in the concept of movement (locomotor, non-locomotor and manipulative) so that the research results from this concept become more complete.